EXTRADITION UNDER INTERNATIONAL LAW - SUGANTHINI, A. (International Journal of Psychosocial Rehabilitation, 2020)
Extradition under International Law deals with the surrender of criminals when they seek Asylum in another country after committing a crime. This Article deals with the conditions under which Extradition can be made. Also with regard to treaties among the Nations with regard to Extradition. Each Nations have their own Extradition Act. India has Extradition Act, 1962 and the same was Amended in the year 1993 as Extradition (Amendment) Act, 1993.